A landscape analysis to understand orientation of honey bee (Hymenoptera: Apidae) drones in Puerto Rico - Galindo Cardona, Alberto (2015)
Honey bees (Apis mellifera L., Apidae, Hymenoptera) show spatial learning behavior or orientation, in which animals make use of structured home ranges for their daily activities. Worker (female) orientation has been studied more extensively than drone (male) orientation. Given the extensive and large flight range of drones as part of their reproductive biology, the study of drone orientation may provide new insight on landscape features important for orientation. We report the return rate and orientation of drones released at three distances (1, 2 and 4 Km) and at the four cardinal points from an apiary located in Gurabo, Puerto Rico. We used high resolution aerial photographs to describe landscape characteristics at the releasing sites and at the apiary. ANOVAs were used to test significance among returning times from different distances and directions. A PCA was used to describe the landscape at the releasing sites and GLMs were used to identify landscape characteristics that influenced the returning times of drones. Our results showed for the first time that drones are able to return from as far as 4 km from the colony. Distance to DCA, orientation, and tree lines were the most important landscape characteristics influencing drone return rate. We discuss the role of landscape in drone orientation.